Menstrual Cycle Characteristics, Hormonal Contraceptive Use, and Perceptions of Related Effects in Resistance-Trained Athletes - SantaBarbara, K; Helms, E; Armour, M; Harris, N (SAGE Publications, 2024)
There has been an increased interest in the effects the menstrual cycle (MC) may have on sports performance. As a part of the MC, many females experience a wide range of symptoms related to hormonal fluctuations and menstrual bleeding, including physical pain and mood disturbances. Currently, there is a lack of data on the MCs of females who participate in resistance training. The dearth of information on the regular MC in female athletes may lead to poorly informed training recommendations which may be detrimental for female athletic advancement. The purpose of this survey was to determine the average MC characteristics, hormonal contraceptive (HC) use and perceived effects of the MC on training in resistance-trained athletes, and to determine if there are differences in these variables when comparing recreationally trained women to competitive-level athletes. A survey addressing questions about the MC, HC use and perceived effects of the MC was accessed by 906 participants who self-identified as resistance-trained athletes. Resistance-trained athletes, competitive or not, experience MCs similar to data on other exercising females and the general population. MC symptoms are widespread and, for some, can be quite severe and limiting. Competitive athletes were not more likely to experience MC irregularities than non-competitive females. Nearly half of the participants reported using HCs. Most participants perceived that their MC had a negative effect on their performance and that their MC caused reductions in training load or workout program adherence, although most competitive-level athletes did not withdraw from competitions due to MC symptoms.
Keywords: 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Women's Health; Clinical Research; Contraception/Reproduction; Pain Research; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; 32 Biomedical and clinical sciences; 42 Health sciences; 52 Psychology